2017
DOI: 10.1590/0100-69912017001011
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of bacterial cellulose membrane for the treatment of lower limbs chronic varicose ulcers: a randomized and controlled trial

Abstract: Objective: to evaluate the efficacy of Bacterial Cellulose (BC) membrane dressings in the treatment of lower limb venous ulcers. Methods: we carried out a prospective, randomized, controlled study of 25 patients with chronic venous ulcer disease in the lower limbs from the Angiology and Vascular Surgery Service of the Federal University of Pernambuco Hospital and from the Salgado Polyclinic of the County Health Department, Caruaru, Pernambuco. We randomly assigned patients to two groups: control group, recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 30 publications
3
25
0
9
Order By: Relevance
“…Beside the treatment of burn wounds, BNC was applied in chronic venous ulcers. There were no infectious complications in the treatment group and, furthermore, less pain and an earlier withdrawal of analgesic medications [120].…”
Section: In Vivo Scaffoldsmentioning
confidence: 80%
“…Beside the treatment of burn wounds, BNC was applied in chronic venous ulcers. There were no infectious complications in the treatment group and, furthermore, less pain and an earlier withdrawal of analgesic medications [120].…”
Section: In Vivo Scaffoldsmentioning
confidence: 80%
“…One example was the study of Almeida and co‐workers that showed that BC used in the form of patches for 24 h did not promote skin irritation (Almeida et al ., ). Also, BC tested for the treatment of chronic varicose ulcers of lower limbs for 120 days showed a decrease in the depth of the ulcer suggesting that BC induced tissue remodelling without associated toxicity (Cavalcanti et al ., ).…”
Section: Biocompatibility Of Bacterial Cellulosementioning
confidence: 97%
“…In order to be defined as elderly, a person must have a chronological age ≥ 65 years in developed countries, or be from 50 to 64 years old and have clinical conditions or physical limitations affecting the ability to walk or to perform activities of daily living, because of their physical fitness or the physiological conditions affected. 14 Therefore, the study enrolled patients over the age of 50 who had chronic venous ulcers classified as CEAP 6 according to the international consensus on chronic venous diseases (open and active ulcers) 15 and who had been diagnosed with the condition by a physician. One patient who had not been diagnosed was enrolled on the study after consultation with a vascular surgeon who confirmed the condition.…”
Section: Methodsmentioning
confidence: 99%